Poverty-Specific Purchasing Power Parities in Africa - Dikhanov, Yuri (World Bank, Washington, DC, 2017)
The paper revisits the issue of poverty-specific purchasing power parities (PPPs), using the most recent (2011) International Comparison Program (ICP) results. The World Bank's global poverty count uses a common international poverty line -- currently $1.90 at 2011 international prices—based on the ICP PPPs for consumption. The use of these PPPs is often criticized for two reasons. First, the ICP PPPs are based on patterns of aggregate household consumption, not the consumption of the poor. Second, the basket of goods and services used for collecting prices for the ICP is not poverty specific. On the first issue, using data from 28 African countries, the paper concludes that the poverty-specific PPPs estimated with household expenditure survey weights are very similar to the ICP PPPs. On the second issue, poverty-specific PPPs were estimated after removing items deemed to be irrelevant for the poor. The overall effect of removing these items from consumption PPPs is shown to be negligible.